Factors affecting haematological profiles in three indigenous Ethiopian sheep breeds - Tibbo, Markos; Aragaw, K.; Abunna, F.; Woldemeskel, M.; Deressa, A.; Dechassa, M.L.; Rege, J.E.O. (Springer, 2005)
Haematological parameters were studied in 377 apparently healthy sheep comprising three indigenous breeds of Ethiopia. The effect of breed, age, gender and season on the haematological values was assessed. There was significant (P<0.01) breed difference for all erythrocytic series. Red blood cells (RBCs) and packed cell volume (PCV) were significantly higher (P<0.01) in Menz than in Wello and Tukur breeds. However, haemoglobin (Hb) concentration was significantly lower (P<0.001) in Menz than in other breeds. Lymphocyte and eosinophil levels were significantly higher (P<0.001) in Menz than in Tukur and Wello breeds. Neutrophil and monocyte concentrations were significantly higher (P<0.001) in Wello and Tukur than in Menz sheep. Gender had no significant (P>0.05) effect on erythrocytic and leukocytic parameters. There was a decrease in lymphocytes with increasing age, whereas the reverse was true for neutrophils. RBCs and PCV were significantly higher (P<0.05) during the dry season than any other seasons. Total white blood cell (WBC) count was significantly higher (P<0.0001) during the long rainy season than during other seasons. The Hb, mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC) of the indigenous breeds were higher than those of exotic sheep breeds. Our study is believed to aid clinical assessment and disease diagnosis in these breeds.